Surgical Outcome after Downstaging in Locally Advanced Breast Carcinoma-A Clinical Study of 50 Cases (KYAMC Journal, 2023)
Background: The number of deaths related to breast cancer is increasing at an alarming pace worldwide. In Bangladesh, the incidence rate of breast cancer was about 22.5 per 100000 females. Almost everyone has a palpable lump, and 40% of them have locally advanced breast cancer. The typical treatment for patients with LABC is neoadjuvant chemotherapy followed by surgery.Materials and Methods: From January 2018 to December 2022, 50 newly diagnosed locally advanced breast cancer (LABC) patients were enrolled in this prospective study at the Bangladesh Medical College Hospital, Dhaka; to assess the clinical and pathological response of the disease after chemotherapy and surgery. The size of the primary tumor and the size of the axillary nodes were measured and compared to the previous record. The patients had a surgery and axillary excision after three to six weeks of neoadjuvant treatment. The pathological response of the primary tumor and axillary node was examined using histopathology. Other biological markers were tested, including the estrogen receptor (ER), progesterone receptor (PR) and Human epidermal growth factor receptor (Her-2).Results: 44 patients (88.0%) responded clinically after four cycles of neoadjuvant chemotherapy, with 7 patients (14.0%) showing complete clinical response (cCR) and 41 patients (82.0%) showing partial response (pCR). In 22 individuals, surgical specimens revealed complete pathological response (cPR) (10 percent).Conclusions: The neoadjuvant chemotherapy schedule for locally advanced breast cancer has good surgical outcome.KYAMC Journal Vol. 13, No. 04, January 2023: 229-233